Research on Mechanical Behavior of Geogrid–Soil Interface Under Rainfall Infiltration - Yongliang Lin; Yingying Wang (Applied Sciences)
With the objective of disaster prevention and the control of geotechnical structures under rainfall environments, an experimental method was adopted to study the mechanical behavior of the geogrid–soil interface. A series of monotonic direct shear tests under different working conditions were carried out to analyze the effects of normal stresses, shear rates and infiltration time on the shear characteristics of the geogrid–soil interface, and to investigate the interaction mechanism of the geogrid–soil interface under rainfall infiltration by means of an independently adapted experimental apparatus to simulate the actual rainfall infiltration situation. The results show that the soil under rainfall infiltration conforms to the Mohr–Coulomb criterion; with the increase in rainfall infiltration time, the peak shear stress at the geogrid–soil interface decreases, and the cohesion and friction angle of the geogrid–soil interface are significantly reduced, and the cohesion decreases by 45.5%, and friction angle decreases by 22.9% when the shear rate is 1.5 mm/min. The research results can provide theoretical and practical guidance for more accurate prediction and response to the effects of rainfall on soil properties in engineering practice. However, the research is only targeted at specific conditions. The variability of geotechnical engineering in aspects such as different soil types, various geosynthetic materials and diverse environmental conditions still needs to be further explored in depth, so as to contribute to the sustainable development of global geotechnical engineering and the effective prevention of disasters.